2020
DOI: 10.7150/ijbs.36407
|View full text |Cite
|
Sign up to set email alerts
|

The NOTCH1-HEY1 pathway regulates self-renewal and epithelial-mesenchymal transition of salivary adenoid cystic carcinoma cells

Abstract: Our previous study demonstrated a close relationship between the NOTCH signaling pathway and salivary adenoid cystic carcinoma (SACC). Its receptor gene, NOTCH1, and its downstream gene, HES1, contribute to the proliferation, invasion and metastasis of SACC. Accumulating evidence supports HEY1 as another effector of the signaling pathway. The purpose of this study was to explore the effects of the NOTCH1-HEY1 pathway on the proliferation, invasion and metastasis of SACC cells. Our results verified that HEY1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…Accumulating evidence provided more insights into CSCs and the complex effects of different signaling pathways may trigger the switch of tumor cells to a stem cell-like phenotype 34 - 36 . While PI3K/AKT and MAPK/ERK signaling pathways have been reported to be responsible for numerous oncogenic properties of lung adenocarcinoma 37 - 39 , yet the mechanistic characterization of self-renewal maintenance in lung cancer stem-like cells by manipulating oncogenic and stem cell signaling pathways remain limited and elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence provided more insights into CSCs and the complex effects of different signaling pathways may trigger the switch of tumor cells to a stem cell-like phenotype 34 - 36 . While PI3K/AKT and MAPK/ERK signaling pathways have been reported to be responsible for numerous oncogenic properties of lung adenocarcinoma 37 - 39 , yet the mechanistic characterization of self-renewal maintenance in lung cancer stem-like cells by manipulating oncogenic and stem cell signaling pathways remain limited and elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The protein matrix metalloproteinases (MMPs) can degrade the extracellular matrix to promote tumor invasion 13 . Previous studies have shown that Hey1 can promote the EMT process and the expression of matrix metalloproteinases expression profile of tumor cells 14 - 16 . Here, Western blotting was used to detect the impact of Hey1 on the expression of EMT-related proteins in A375 cells.…”
Section: Resultsmentioning
confidence: 98%
“…Notch1 was predicted to be a potential target of miR-34a based on miRs target prediction software (TargetScan, PicTar, and miRBase). e Notch1 signaling pathway is an apoptosis-related pathway that is involved in the apoptosis of various cell types [39][40][41]. Notch1 acts as an endogenous myocardial protective factor through the RISK/SAFE/HIF-1 alpha signaling, which reduces myocardial intracellular reactive oxygen species (ROS), enhances the myocardiocytes vitality, and significantly reduces the myocardial ischemia reperfusion injury [42].…”
Section: Discussionmentioning
confidence: 99%